Structuring the Greening of Tourism Areas Developing the "Sweembath" Naga Sopa Tourism Village Realizes Community Welfare - Susilo, Hariadi; Dardanila; Suwilo, Saib; Tulus; Tafsin, Ma’ruf; Patriani, Peni; Tugiman; Ariani, Farida; Silalahi, Amlys Syahputra; Nur’ainun (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Arrangement of Reforestation of Tourism Areas for the development of the "Sweembath" Naga Sopa Tourism Village, Bandar Huluan District, Simalungun Regency to Realize Community Welfare. The preliminary survey shows the need for further development so that it is expected to improve the welfare of the village community. The method of implementing the assisted villages is carried out with a participatory approach from the community managing the tourist area, elements of the Village/District apparatus and other relevant stakeholders. In-depth discussion and interview techniques are carried out to explore the root of the problem and developments in the short/long term that can be implemented or expected. the results of the implementation of plant arrangement, namely: (1) Reforestation of the Sweembat area (2) Focus Group discussion (3) Reforestation in the "sweembat" area (3) Mutual cooperation with the community (4) Arrangement of plants for reforestation (5) Installer of Simalungun Assisted Village Plank